Afterdischarges following M waves in patients with voltage-gated potassium channels antibodies - Jingwen Niu; Hongzhi Guan; Liying Cui; Yuzhou Guan; Mingsheng Liu (Clinical Neurophysiology Practice, 2017)
Objective: To explore the correlation between afterdischarges in motor nerve conduction studies and clinical motor hyperexcitability in patients with voltage-gated potassium channels (VGKC) antibodies. Methods: Six patients with positive serum antibodies to contactin-associated protein-like 2 (CASPR2) or/and leucine-rich glioma-inactivated protein 1 (LGI1) were recruited, including 5 with autoimmune encephalitis, and 1 with cramp-fasciculation syndrome. Electromyography (EMG), nerve conduction studies (NCS) and F waves were performed, and afterdischarges were assessed. One patient was followed up. Results: Five patients had clinical evidence of peripheral motor nerve hyperexcitability (myokymia or cramp), and four of them had abnormal spontaneous firing in concentric needle electromyography (EMG). Prolonged afterdischarges following normal M waves were present in all six patients, including the two patients who had no EMG evidence of peripheral nerve hyperexcitability (PNH). Afterdischarges disappeared after treatment with intravenous immunoglobulin (IVIG). Conclusion: The afterdischarges in motor nerve conduction study might be a sensitive indicator of peripheral motor nerve hyperexcitability in patients with VGKC antibodies. Significance: Afterdischarges in motor nerve conduction study might be more sensitive than needle electromyography for detecting peripheral motor nerve hyperexcitability, and could disappear gradually in accordance with clinical improvement and reduction of antibodies. Keywords: Afterdischarges, VGKC, Autoimmune encephalitis, Peripheral nerve hyperexcitability, F wave, M wave